Damage evolution in Al wire bonds subjected to a junction temperature fluctuation of 30 K - Agyakwa, Pearl; Yang, Li; Arjmand, Elahjeh; Evans, Paul; Corfield, Martin; Johnson, Christopher Mark (Springer, 2016)
Ultrasonically bonded heavy Al wires subjected to a small junction temperature fluctuation under power cycling from 40°C to 70°C were investigated using a non-destructive three-dimensional (3-D) x-ray tomography evaluation approach. The occurrence of irreversible deformation of the microstructure and wear-out under such conditions were demonstrated. The observed microstructures consist of interfacial and inter-granular cracks concentrated in zones of stress intensity, i.e., near heels and emanating from interface precracks. Interfacial voids were also observed within the bond interior. Degradation rates of ‘first’ and ‘stitch’ bonds are compared and contrasted. A correlative microscopy study combining perspectives from optical microscopy with the x-ray tomography results clarifies the damage observed. An estimation of lifetime is made from the results and discussed in the light of existing predictions.